Elements of the legal personаlity in the civil law - Надьон, В. В. (Problems of legality, 2014)
In this paper, an analysis of the question of legal personality. Disclosed structural elements of personality, through which characterized the essence and significance of personality. Made relevant theoretical conclusions, proposed practical recommendations on this issue.